Missionary activities of the Orthodox Church in Kazakhstan (Journal of Philosophy Culture and Political Science, 2015)
The history of Russian Orthodox Church placememt among Kazakhs is a complex and controversial issue connected to the ultimate changes in political, economic and spiritual life of Kazakh people after affiliation of Kazakhstan with the Russian state. Missionary movement was an important constituent of the policy of Russian government towards Kazakhstan. Missionary activity is closely related to the Christianization of non-Russian peoples, monastic colonization. The author of the article attempts to provide objective disclosure of the peculiarities of the approaches, types, forms, contents and effectiveness of missionary activity of Orthodox Church, social function of the church in social, cultural, spiritual and moral life of the society, and identify essential factors of missionary activities of Russian Orthodox Church.Key words: missionary outreach, Orthodox missionary outreach, mission, missionary activity, proselytism, proselyte, missionary field, methods and forms of missionary activity.